DIGITAL DA’WAH FOR SANTRI AS A REVITALIZATION IN SOCIAL 5.0 - Chanifah, Nur; Rohmah, Siti (UPT. PKM UB, 2022)
The current development of information and communication technology has triggered a digital transformation that has changed the industrial order. If in the Industrial 4.0 era technology was only placed as a machine or tool to access information, then in the Social 5.0 era technology and its functions have been emphasized more as part of human life. Islamic boarding schools as educational institutions are currently also required to be able to accelerate and transform according to these developments. If previously the da'wah media was more conventional with a very limited reach, now it is hoped that santri can expand their da'wah by using digital media so that their contribution can reach all levels of society. This is an opportunity and a challenge for Islamic boarding schools in developing da'wah. This activity uses a personal approach by providing understanding to caregivers and administrators of the Tahfidz Al-Quran Islamic Boarding School Merjosari Lowokwaru Malang